Fear of cancer recurrence following allogeneic haematopoietic stem cell transplantation (HSCT) for haematological malignancy: A cross-sectional study. (December 2020) - Brice, Lisa; McErlean, Gemma; Donovan, Caroline; Tapp, Caley; Gilroy, Nicole; Kabir, Masura; Greenwood, Matt; Larsen, Stephen R.; Moore, John; Gottlieb, David; Hertzberg, Mark; Brown, Louisa; et al.
Abstract: Purpose: The aim of this study was to quantify the prevalence of Fear of Cancer Recurrence (FCR) in patients with a prior haematology malignancy surviving more than one year post allogeneic haematopoietic stem cell transplantation (HSCT), and to identify the demographic, medical and psychological factors associated with FCR occurrence. Method: Participants were adult allogeneic HSCT recipients who had undergone the procedure for acute leukaemia or other haematological malignancy between the years 2000–2012 in Sydney, Australia. They completed a purpose designed survey and six other validated instruments which assessed FCR, psychological functioning, quality of life, demographic, social and clinical variables. Results: Of the 364 respondents, approximately 11% of the sample lived with severe FCR while only 5% of subjects reported having no FCR. Variables significantly associated with higher FCR included unemployment, a shorter time (years) post-transplant, not attending to health screening (PAP smear), a secondary diagnosis of skin cancer, younger age, referral to a psychiatrist and taking psychotropic medication. Higher psychological distress (depression, anxiety, stress) and lower quality of life made a significant contribution to the prediction of FCR. Conclusions: Post HSCT follow-up care should include an assessment and discussion regarding FCR to balance both realistic and unrealistic cancer recurrence risks. Managing FCR is one of the most ubiquitous unmet needs of survivors of haematological disease and it is important that HSCT nurses are both aware of the fear, and are equipped with knowledge on how to help patients navigate it with realistic expectations. Highlights: Survivors of HSCT for haematological malignancy are at risk of relapse and secondary cancers. Very few (5%) survivors reported no symptoms suggestive of a fear of cancer recurrence (FCR). Higher FCR was associated with unemployment, younger age, less time lapse since BMT, psychiatry input and psychotropic drug use. Validated measures of psychological distress and decreased quality of life significantly predicted FCR. Many HSCT survivors live with fear of cancer recurrence (FCR); it is important that HSCT nurses are skilled in managing it.